Pelatihan dan Pendampingan Pengolahan Susu Pasteurisasi pada Kelompok Peternak Sapi Perah Langgeng Mulyo Desa Ngenep - Nonok Supartini; Ahmadi Kgs; Sumarno; Melani Windiarti (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Milk is a food product that is easily destroyed, therefore it needs to be handled or processed. One form of milk processing is pasteurized milk. The Langgeng Mulyo Farmer's Group is a group of dairy cows that have only produced fresh milk without being processed. Efforts to diversify dairy products are carried out by involving wives from the Langgeng Mulyo Farmer group. It is hoped that the women of the farmer’s group are productive, and can increase family income. This community dedication activity is carried out by means of training and assistance in processing pasteurized milk. Training and counseling on pasteurized milk processing is carried out using simple methods and simple equipment. The training activities include handling post-dairy milk with pasteurization, training on proper heating methods to kill bacteria using simple tools, product packaging. So that the absorption of the technology provided can be absorbed and applied, after the training, mentoring is carried out where participants try their own pasteurized milk processing. The results of the evaluation of the training and mentoring activities for processing pasteurized milk 95% of the participants have been able to apply the material provided.